DIGITAL INTERVENTIONS FOR ADOLESCENT DEPRESSION AND ANXIETY: NARRATIVE REVIEW AND FUTURE DIRECTIONS - Ewa Szczęsna; Marta Miejska-Kamińska; Izabella Sośniak; Lidia Jurczenko (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Adolescence is a critical developmental stage during which individuals are particularly vulnerable to mental health challenges, including depression and anxiety. Despite their high prevalence, access to traditional mental health care remains limited for many adolescents. Purpose of the study: This narrative review aims to synthesize current evidence regarding the effectiveness of digital interventions—such as mobile applications, internet-based cognitive behavioral therapy (iCBT), conversational AI, gamified tools, and peer-support platforms—in reducing symptoms of depression and anxiety among adolescents. Materials and methods: A comprehensive literature review was conducted, including 35 peer-reviewed studies and systematic reviews published between 2015 and 2025. Sources were identified using PubMed and Scopus databases, focusing on digital mental health tools targeting individuals aged 10–24 years. Conclusions: Digital mental health interventions show promising efficacy in addressing adolescent depression and, to a lesser extent, anxiety. Evidence supports their potential for increased accessibility, user engagement, and stigma reduction. However, gaps remain in standardization, cultural adaptation, and long-term evaluation. Further research should address these limitations and guide the integration of digital tools into youth mental health care systems.